Killing Custer the Battle of the Little Bighorn and the fate of the Plains Indians - Welch, James 1940-2003; Stekler, Paul Jeffrey (Penguin Books, 1994)
Nonfictionalized account, from the Indian point of view, of Custer's attack on the Plains Indians in 1876.